Differentiating between viruses and virus species by writing their names correctly - Zerbini, Francisco Murilo; Siddell, Stuart G.; Mushegian, Arcady R.; Walker, Peter J.; Lefkowitz, Elliot J.; Adriaenssens, Evelien M.; Alfenas-Zerbini, Poliane; Dutilh, Bas E.; García, María Laura; Junglen, Sandra; Krupovic, Mart; Kuhn, Jens H.; et al. (Archives of virology, 2022)
Following the results of the International Committee on Taxonomy of Viruses (ICTV) Ratification Vote held in March 2021, a standard two-part "binomial nomenclature" is now the norm for naming virus species. Adoption of the new nomenclature is still in its infancy; thus, it is timely to reiterate the distinction between "virus" and "virus species" and to provide guidelines for naming and writing them correctly.